Tetrazine Assists Reduction of Water by Phosphines: Application in the Mitsunobu Reaction. Issue 39 (18th August 2016) - Polezhaev, Alexander V.; Maciulis, Nicholas A.; Chen, Chun‐Hsing; Pink, Maren; Lord, Richard L.; Caulton, Kenneth G.
Abstract: Reaction of 3, 6‐disubstituted‐1, 2, 4, 5‐tetrazines with water and PEt3 forms the corresponding 1, 4‐dihydrotetrazine and OPEt3 . Thus PEt3, as a stoichiometric reductant, reduces water, and the resulting two reducing equivalents serve to doubly hydrogenate the tetrazine. A variety of possible initial interactions between electron‐deficient tetrazine and electron‐rich PR3, including a charge transfer complex, were evaluated by density functional calculations which revealed that the energy of all these make them spectroscopically undetectable at equilibrium, but one of these is nevertheless suggested as the intermediate in the observed redox reaction. The relationship of this to the Mitsunobu reaction, which absorbs the components of water evolved in the conversion of alcohol and carboxylic acid to ester, with desirable inversion at the alcohol carbon, is discussed. This enables a modified Mitsunobu reaction, with tetrazine replacing EtO2 CN=NCO2 Et (DEAD), which has the advantage that dihydrotetrazine can be recycled to tetrazine by oxidation with O2, something impossible with the hydrogenated DEAD. For this tetrazine version, a betaine‐like intermediate is undetectable, but its protonated form is characterized, including by X‐ray structure and NMR spectroscopy. Abstract : Tetrazine is a redox mediator that enables the transfer of the PR3 reducing power to the protons of water. The reaction sequence continues with the formation of R3 PO and dihydrotetrazine. In the presence of strong acid phosphine/tetrazine pairs, tetrazinium salts are formed. This enables a modified Mitsunobu reaction, with tetrazine replacing EtO2 CN=NCO2 Et (DEAD), with the advantage that dihydrotetrazine can be recycled to tetrazine by oxidation with HNO2 .